Distinct Signaling Functions of Rap1 Isoforms in NO Release From Endothelium - Kosuru, Ramoji; Singh, Bandana; Lakshmikanthan, Sribalaji; Nishijima, Yoshinori; Vasquez-Vivar, Jeannette; Zhang, David X.; Chrzanowska, Magdalena (Frontiers in Cell and Developmental Biology, 2021)
Small GTPase Rap1 plays a prominent role in endothelial cell (EC) homeostasis by promoting NO release. Endothelial deletion of the two highly homologous Rap1 isoforms, Rap1A and Rap1B, leads to endothelial dysfunction ex vivo, and hypertension in vivo. Mechanistically, we showed that Rap1B promotes NO release in response to shear flow by promoting mechanosensing complex formation involving VEGFR2 and Akt activation. However, the specific contribution of the Rap1A isoform to NO release and the underlying molecular mechanisms through which the two Rap1 isoforms control endothelial function are unknown. Here, we demonstrate that endothelial dysfunction resulting from knockout of both Rap1A and Rap1B isoforms is ameliorated by exogenous L-arginine administration to rescue NO-dependent vasodilation and blood pressure. We confirmed that Rap1B is rapidly activated in response to agonists that trigger eNOS activation, and its deletion in ECs attenuates eNOS activation, as detected by decreased S1177 phosphorylation. Somewhat surprising was the finding that EC-deletion of Rap1A does not lead to impaired agonist-induced vasodilation ex vivo. Mechanistically, the deletion of Rap1A led to elevated eNOS phosphorylation both at the inhibitory, T495, as well as the activating S1177 residues. These findings indicate that the two Rap1 isoforms act via distinct signaling pathways: while Rap1B directly positively regulates eNOS activation, Rap1A prevents negative regulation of eNOS. Notably, the combined deficiency of Rap1A and Rap1B has a severe effect on eNOS activity and NO release with an in vivo impact on endothelial function and vascular homeostasis.